NEW INDICATORS OF HSP27 FUNCTIONAL STATE IN BREAST CANCER CELLS WITH DIFFERENT VARIANTS OF HER2/NEU-STATUS - E. V. Kaigorodova; M. V. Bogatyuk; M. V. Zavyalova; N. A. Tarabanovskaya; E. I. Simolina; E. M. Slonimskaya; E. L. Choynzonov; V. M. Perelmuter (Сибирский онкологический журнал)
New and original values (coefficient of phosphorylation and coefficient of intracellular distribution) proposed. They are reflecting a functional state of the heat shock protein 27 kDa (Hsp27) in tumor cells of breast cancer. These coefficients are more clearly reflect the functional state of Hsp27, than classical evaluation of chaperone expression only in the cytoplasm. It has been shown that in tumors with high expression of receptor Her2/neu on the membrane in the absence of gene amplification cerb2/neu (Her2/neu (3+) FISH (-)) there are low coefficients of phosphorylation and intracellular distribution as compared with Her2/neu-positive (Her2/neu (2+/3+) FISH (+)) and Her2/neu-negative tumors (Her2/neu (0/1+) FISH (-)). The possible molecular mechanisms of the phenomenon of dissonance cerb2 / neu gene amplification and receptor Her2/neu expression on the membrane of tumor cells breast cancer are discussing.